Tenants' rights and the Renting Homes (Wales) Act 2016. Issue 4 (2nd October 2019) - Huws, Catrin Fflur
Abstract: Following the devolution of powers by the UK Government to the National Assembly for Wales, the law in Wales has diverged considerably from the law in England on many issues, including housing policy. In Wales, recent housing policy and law focused on the improvement of housing quality and on the equalisation of the relationship between the housing provider and the housing occupier in order to ensure that those living in rented accommodation have a better awareness of their rights and clearer and more accessible paths to obtain redress. This article introduces the key provisions of the Renting Homes (Wales) Act2016 and explains the changes it makes to the regulation of the public and private domestic rental sector in Wales. It aims therefore to outline the main changes made to the law as between England and Wales, and also aims to highlight why an increased consumer protection focus could improve the housing sector but brings with it the risk of stymieing the housing market by increasing costs and decreasing housing availability through over regulation. The paper identified how lessons from Wales may have implications for the improvement of tenant rights in other national housing markets.